Anisotropic MWCNT/polyimide aerogels with multifunctional EMI shielding and strain sensing capabilities. (December 2022) - Ma, Shengqi; Jia, Tingting; Wang, Chengyang; Xu, Huikang; Zhou, Hongwei; Zhao, Xiaogang; Chen, Chunhai; Wang, Dezhi; Liu, Changwei; Qu, Chunyan
Graphical abstract: A series of anisotropic composite polyimide aerogels (CPIAs) is designed and synthesized. Using unidirectional freeze-drying method allows CPIAs demonstrated unique electromagnetic shielding and strain responsive behaviors. The CPIAs possess excellent shielding behavior reach up to 99.4 dB, and a stable responsiveness in a wide temperature range from 25 °C to 316 °C. Highlights: A strategy for design of anisotropic composite aerogels (CPIAs) is proposed. The CPIAs possess excellent electromagnetic shielding behaviors. The CPIAs exhibit stable strain response performance from 25 °C to 316 °C. A strain alarm system was assembled by CPIA-4. Abstract: The demand for electromagnetic interference (EMI) shielding materials has become increasingly urgent due to the widespread application of electronic communication and devices. Herein, anisotropic composite polyimide aerogels (CPIAs) were prepared via unidirectional freeze-drying method using PI as the polymer matrix and MWCNTs as the filler. These CPIAs demonstrated excellent shielding behavior with an average shielding effectiveness value of 84.2 dB (CPIA-4) in the X-band. Owing to its anisotropic microstructure, an idealized model for determining the attenuation constant was proposed. The CPIA also works effectively as a lightweight sensitive strain sensor (gauge factor of 1.23 and stability cyclic testing over 1000 cycles). Remarkably, the CPIAs maintained stable response performance across a wide temperature range (25, 177, and 316 °C) and good performance when assembled into a strain alarm system, indicating promising potential for applications in harsh environments such as arc-shaped structure radar patch shielding materials or landing protection devices for aerobats.